Pengembangan Perangkat Pembelajaran IPS SMP/MTs Kelas VIII untuk Melatih Keterampilan Sosial Siswa - Ana Kamilah; A. Fatikhul Amin Abdullah (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
Many students put down Social Studies as boring class, because the learning model is less variable and poor of media. So that the development of learning media in the form of Student Textbooks (Buku Ajar Siswa) is made. The study design using type 4-D (define, design, develop, disseminate) development and research plan one group pretest-posttest design. The collection data method is observation, test, and quetionnaires. in trial of textbook difficulty level in category at very low or very easy to understand and can be regarded as reliable instrument to measure feasibility RPP quality. Average score in each social skill including contributing ideas/opinions, being good listener, and respecting friend’s opinion was 89,69; 90,44; 90,03, which is on very high category. The student response toward components, newness, ease of understand, and practicing social skill of the device obtained percentage in a row was 72,92%, 79,69%, 79,69%, 65,63%, which shows the response of the student is very high. The study concludes that the learning device has high efecctiveness and quality to improve the study result and student’s social skill. Based on this research, so that it can be used by social studies teachers in order to develop devices according to the nature of the material being taught to suit the learning objectives.